2010
DOI: 10.1590/s1517-83822010000100016
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Listeria monocytogenes on stainless steel surface and biotransfer potential

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 43 publications
1
33
0
4
Order By: Relevance
“…37 Thus, there is a high probability that the irreversibly adhered cells will remain even after hygienization. 33 This is one of the main reasons for biofilm formation on surfaces in contact with food.…”
Section: Biofilm Formation At 27°cmentioning
confidence: 99%
“…37 Thus, there is a high probability that the irreversibly adhered cells will remain even after hygienization. 33 This is one of the main reasons for biofilm formation on surfaces in contact with food.…”
Section: Biofilm Formation At 27°cmentioning
confidence: 99%
“…It can be found in food such as ready-to-eat sandwiches, salads, and sprouts and in food processing environments, on equipment such as delicatessen slicers and in milk storage tanks (20,28). The occurrence of foodborne outbreaks as well as sporadic cases caused by this bacterium can be attributed to its increased ability to survive in food processing environments through biofilm formation (29,30). L. monocytogenes is commonly known to survive in biofilms in these environments, as a result of insufficient cleaning protocols compounded by the ability of the microorganism to resist chemical disinfection (5,7,13,31).…”
Section: Discussionmentioning
confidence: 99%
“…The location of bacterial biofilms and cell attachment can be directly responsible for the ability of the organism to evade detection. Mechanical release through swabbing relies on the ability to make direct contact with the biofilm structure, but this may not possible in pores, grooves, scratches, and other surface features; this creates the potential for the biotransfer of pathogenic bacteria, especially L. monocytogenes and even spoilage microorganisms, to food products that come into contact with the contaminated surface during processing (29). Sonication does not need direct physical contact with the biofilm, as does swabbing, to facilitate the release of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The Listeria may persist in food plants for months and up to several years [18]. It has been demonstrated that the rapid adhesion of this bacterium to a surface, combined with biotransfer potential throughout the biofilm formation stages, makes L. monocytogenes a potential risk for the food industry; cells can easily be transferred to food products during processing [4]. Biofilm formation and growth can continue on the surface of foods leading to outbreaks of listeriosis.…”
Section: Introductionmentioning
confidence: 99%